Bandung conference 1955 and Bandung commemorative conferences 2005 and 2015: excerpts from the declarations of heads of state and governments - (:unkn) unknown (My University, 2018)
Under the auspices of Indonesian government, States of Africa and Asia have been involved in the 1955 Bandung Asian-African conference and its commemorative conferences in 2005 and 2015. At every conference, they produced an official statement, communiqué or declaration. This article is aimed at presenting briefly the content of those documents. It is not intended to review the whole documents in exhaustive way, but to quote the passages considered to be significant in relation to the evolution of socio-cultural and politico-economical situation in Africa and Asia during the last 60 years. Ref. Darwis Khudori, BANDUNG LEGACY AND GLOBAL FUTURE: New Insights and Emerging Forces, New Delhi, Aakar Book, 2018, 16cm x 23.5cm, 304p. ISBN 978-93-5002-549-9, pp. 291-298.
Keywords: African Research